THE EVALUATION OF EDUCATION PROGRAM IMPLEMENTATION ON HEAD OF INDONESIAN REPUBLIC BANK UNIT - Afrizal Y.; Bedjo Sujanto; Makruf Akbar (Program Studi S3 Ilmu Manajemen, 2017)
This study aims to evaluate education programs head of Indonesia Republic Bank (BRI) Unit head in Pekanbari Regional Office at BRI Corporate University Padang. The study conducted for six months (October 2015 up to March 2016) using CIPP evaluation model. The results showed that educational programs of head of BRI Unitis already well underway in accordance with the educational programs that have been compiled. Nevertheless, it is necessary to evaluate on the improvement of the competence of the Head of BRI in the workplace after attending the educational process and the impact of education programs to the banking business. Recommendations are given for the improvement of the education programs is to revise the Instructional Systems Design so that the effectiveness of the educational program after participants return to their bases can be evaluated. Keywords: Evaluation, CIPP Model, Educational Program, Bank BRI